Willingness to participate in combined breast and cervical cancer screening and its influencing factors among 35 - 64 year old women participating in screening in Jinan city, 2024: a cross-sectional survey - Hongsheng SONG; Zeyun ZHAO; Cuiyu GONG; Fei ZHU; Xuelian ZHAO; Li ZHANG; Fanghui ZHAO; Yuping WANG (Zhongguo gonggong weisheng, 2025)
ObjectiveTo investigate the awareness and satisfaction of women in Jinan, Shandong Province, regarding breast and cervical cancer screening programs, and to analyze their willingness to participate in combined screening for both cancers and the influencing factors, with the aim of providing a reference for promoting combined screening for these cancers. MethodsUsing cross-sectional survey methods with a self-developed questionnaire, face-to-face interviews were conducted with 569 women aged 35 - 64 years in Jinan city, Shandong province, from May to July 2024. Participants were recruited through community-based cervical and breast cancer screening programs. The survey collected data on demographic characteristics, awareness of dual-cancer screening, willingness to participate in combined screening, and satisfaction. Data were analyzed using chi-squared tests and binary logistic regression. ResultsA total of 541 valid responses were received. Of the respondents, 87.43% were aware that the government regularly provides free screening for two cancers for women of appropriate age. In addition, 93.16% and 80.78% of respondents were aware of at least one recommended screening method for breast and cervical cancer programs, respectively. For breast cancer screening, awareness of specific methods was as follows: breast examination (79.11%), breast ultrasound (66.54%), and mammography (10.35%). For cervical cancer screening, awareness rates were: HPV testing (74.86%), cytology testing (34.01%), and colposcopy (29.57%). Regarding screening preferences, 77.63% of subjects preferred a single-visit model ("complete both screenings at the same time"), while 17.74% preferred separate visits. Multiple logistic regression identified two independent factors influencing willingness to participate in joint screening: occupation (odds ratio [OR] = 2.63, 95% confidence interval [95%CI]: 1.11 - 6.23) and prior awareness of screening (OR = 6.29, 95%CI: 3.80 - 10.40). Regarding logistics, 99.26% of subjects preferred screening every 1 - 3 years and 71.90% preferred nearby community health centers. Even with full self-payment, 53.05% remained willing to choose community screening. Satisfaction rates were high: 73.94% (process arrangement), 73.57% (technical level of staff), and 72.83% (service attitude). Finally, 98.89% reported that it was convenient to participate. ConclusionsWhile most women demonstrate awareness and willingness to participate in combined breast and cervical cancer screening, targeted health education remains necessary. Further research is needed to assess the feasibility of implementing this model in different regional settings.